Mengembangkan Konten Menarik Sebagai Strategi Branding @Folkative - Viriyaputra, Kevin; Sari, Wulan Purnama (Prologia, 2024)
In the era of social media, it is very easy for us to share various things via Kit's social media accounts, which is also what Folkative's social media accounts do. When discussing social media in this research, researchers want to focus on Instagram, which is one of the most common or widely used social media. Folkative is an online media platform that operates in the field of using the social network Instagram as a medium for transmitting information. New media, which includes the emergence of computer, digital or network technology and communication at the beginning of the 21st century, is called new media or new media. Technology almost always described as new media, especially digital, which often has the characteristics of being tractable, compact, networked, impartial, and interactive. The Folkative Instagram account is intended as an Instagram account to provide information specifically to the younger generation z. This research aims to analyze Folkative's social media using Analisa.io software. The approach used is a qualitative approach using social media content analysis as a data collection method. The research object is branding and the research subject is Folkative's Instagram account. The research results show that Folkative's branding strategy as an information medium can present interesting content, because the language is easy to understand and the information conveyed by Folkative is very concise and clear which is attractive to generation z. Di era media sosial sangat mudah untuk kita berbagi berbagai hal lewat akun media sosial kit itu juga yang di lakukan akun media sosial Folkative. Ketika membahas media sosial dalam penelitian ini, peneliti ingin fokus pada.Instagram adalah salah satu platform media sosial yang paling digandrungi generasi saat ini. Folkative merupakan platform media online  yang bergerak di bidang penggunaan jejaring sosial Instagram sebagai media transmisi informasi.Media baru, yang mencakup munculnya teknologi dan komunikasi komputer, digital atau jaringan pada awal abad ke-21, disebut dengan istilah yaitu new media atau media baru.Teknologi hampir selalu digambarkan sebagai media baru, khususnya digital, yang seringkali memiliki ciri khas penurut, padat, berjejaring, tidak memihak, dan interaktif. Akun Instagram Folkative dimaksudkan sebagai akun Instagram untuk memberikan informasi secara khusus kepada  generasi muda z. Penelitian ini bertujuan untuk menganalisa media sosial Folkative menggunakan software Analisa.io, Pendekatan yang digunakan adalah pendekatan kualitatif dengan mengunakan analisis isi media sosial sebagai metode pengambilan data. Objek penelitan adalah branding dan subjek penelitian nya adalah akun Instagram Folkative. Hasil penelitian menunjukkan bahwa strategi branding Folkative sebagai media informasi dapat menyajikan konten-konten yang menarik, karena bahasa yang mudah di mengerti dan juga penyampaian informasi yang disampaikan oleh Folkative singat padat dan jelas yang menarik untuk generasi z.